PENERAPAN MODEL TEAM BASED LEARNING MELALUI PROYEK PEMBUATAN FILM DOKUMENTER DALAM MENINGKATKAN EFEKTIVITAS MAHASISWA PADA MATA KULIAH TEORI - Pratama, Amor Seta Gilang; Nopiansyah, Radius; Utama, Galuh Tulus; Mustafa, Hanif Risa; Pradita, Dennys (Dharmas Education Journal (DE_Journal), 2024)
The purpose of this research is to see the effectiveness of learning theory courses through the application of Team Based Learning. This departs from the tendency of students to choose practical courses over theoretical courses, resulting in a lack of theoretical knowledge. There needs to be a strategy to make theoretical courses more interesting for students. So the Team Based Learning learning model is applied to increase learning effectiveness in theoretical courses. Learning effectiveness is a quality standard of education as measured by the achievement of learning objectives. This research uses a qualitative descriptive research method with a class action approach through the application of the Team Based Learning model. In this learning model, students work on projects with documentary film results. This research focuses on observations of two groups in the socio-anthropology of art course class of the Jambi University Sendratasik Study Program. In this Team Based Learning model, the lecture is divided into four stages. Namely the theoretical introduction, field work, making scripts, and the editing process. This study found that the application of the Team Based Learning model was able to increase student effectiveness in the socio-anthropology of art theory course.